A new swift method for ram ejaculate enrichment - PIPERELIS (Σ.Γ. ΠΙΠΕΡΕΛΗΣ), S. G.; Vafiadis (Δ. ΒΑΦΕΙΑΔΗΣ), D.; Alexopoulos (Κ. ΑΛΕΞΟΠΟΥΛΟΣ), C. (Journal of the Hellenic Veterinary Medical Society, 2018)
Semen availability in ram semen production facilities is of great importance and a method that would increase viability in low viability ejaculates could be useful. In this study the possibility of a glass beads filtration method estimating the beads total surface provided (TSP) for adhesion of spermatozoa is evaluated. Initially, two different TSP (102cm2,154cm2) achieved by various sizes of beads were tested and no significant difference in viability improvement appeared for the same TSP by different beads (p<0.05). An optimization test followed in which three different funnels were evaluated using standard TSP (154cm2). The only parameter improved was filtrate volume, while filtration time, density and viability improvement remained the same (p<0.05). Finally, different TSP were evaluated and significant differences in viability improvement (p<0.01) and filtrate volume (p<0.05) for 102cm2 appeared. Increase in initial value 25% for viability and ejaculate recovery 65% all in time less than 6 minutes strongly suggest that through further development this method can be used in ram semen production facilities.